John O'Hara - American Writers 80 : University of Minnesota Pamphlets on American Writers - Walcutt, Charles Child, 1908-1989 (Book collections on Project MUSE., 1969)
John O'Hara - American Writers 80 was first published in 1969. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.